USING GAMES TO IMPROVE ENGLISH LANGUAGE SKILLS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The integration of games into English language teaching has become an increasingly popular approach in modern pedagogy. This article examines how gamebased learning contributes to the development of key language skills, including listening, speaking, reading, and writing. The study analyzes psychological, pedagogical, and linguistic foundations of using games in the classroom and evaluates their impact on learner motivation, confidence, and retention. Various types of games—traditional, communicative, and digital—are discussed with practical classroom applications. The paper argues that games are not merely entertaining tools but structured learning strategies that enhance communicative competence and longterm language acquisition.